2021
DOI: 10.33394/jollt.v9i2.3530
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Listening Comprehension Through Frozen 2 Movie

Abstract: As an international language, English has become one of the most commonly spoken languages globally, and mastering the English language is necessary for us. This research aimed to answer the research question, namely Enhancing Listening Comprehension Through Frozen 2 Movie. The researcher wants to know whether using the Frozen 2 movie will help students in increasing their listening comprehension or not. This research using a case study of pre-experimental as the research design. The study involved 16 particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Students revealed that watching movies more often can improve their language skills-especially in listening comprehension. In the previous study, Hamidah and Hadi (2021) found that watching movies can expose students to different accents. It is in line with the result, one student (HA1)…”
Section: Impacts Of Using An English Movie On Students' Listening Skillmentioning
confidence: 95%
See 1 more Smart Citation
“…Students revealed that watching movies more often can improve their language skills-especially in listening comprehension. In the previous study, Hamidah and Hadi (2021) found that watching movies can expose students to different accents. It is in line with the result, one student (HA1)…”
Section: Impacts Of Using An English Movie On Students' Listening Skillmentioning
confidence: 95%
“…Since English is not their native language, Indonesian students found watching English movies a familiar and enjoyable activity, but it required dedicated practice to master listening skills (Putri et al, 2023). Volume 14, Number 2, October 2023, 206-225 As aforementioned, Hamidah and Hadi (2021) say that movies as a learning medium in EFL can help teachers present the language learning material more easily, and students will be more interested in the learning process. Moreover, watching movies can improve students' listening skills.…”
Section: The Impact Of Watching Movies On Students' Listening Skillsmentioning
confidence: 99%